Theory and Problems of College Mathematics - Ayrex Jr., Frank; Philip A. Schmidt (New York : McGraw Hill Education, 1992)
This book is designed primarily to assist students in acquiring a more thorough knowledge and proficiency in basic college mathematics. It includes a thorough coverage of algebra, plane trigonometry and plane analytic geometry .
Part1. Algebra -- Part2. Topics in discrete mathematics -- Part3. Trigonometry -- Part4. Analytic geometry -- Part5. Introduction to calculus .
Includes index.
Keywords: MATHEMATICS